Null-Subject Properties of Slavic Languages With Special Reference to Russian, Czech and Sorbian - Lindseth, Martina (Slavistische Beitraege, 1998)
In the series Slavonic Contributions Slavic dissertations of German-speaking countries as well as occasionally also American, English and Russian are published. In addition, the series provides a forum for anthologies and monographs of established scientists.